Influence of MM and MMD on rheological properties of epoxy resins - P. V. Surikov; A. I. Trofimov; E. I. Kohan; L. K. Sheulova; I. D. Simonov-Emelianov (Тонкие химические технологии)
The molecular characteristics of diane epoxy oligomers produced by industries: DER-330, ED-20, ED-16, ED-8 is studied. The fractional composition was identified. The viscosity characteristics epoxy resins at different temperature are studied the entire range of molecular weight and molecular-mass distribution.